Hidden climate change related risks for the private sector - Brunsmeier, Annette; Groth, Markus (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
Climate change related risks impact and challenge the private sector in many different ways. This also applies to risk drivers like a companies’ reputation and a changing consumer behavior. Since significant risk drivers for companies differ just as much as companies themselves, a sector specific guideline to evaluate possible climate change related risk drivers is indispensable. Further, a sector specific analysis on these risk drivers can foster cross sectoral cooperation, innovation and learning processes with regard to climate change related risks.
Keywords: Business Sector; Climate Change Adaptation; Climate Change Impact; Consumer Behavior; 330 Wirtschaft